Propuesta de diseño de adaptación del tambor del sistema de elevación para transporte de personal de la mina El Silencio (2021)
The adaptation and modeling, in 3D software, of a drum for the lifting system for personnel transport at zero level (0) is proposed, to improve the conditions of entry, to the pit, of the workers of the El Silencio mine. Taking into account the operating parameters, load requirements, safety conditions and aspects related to the structural integrity of the system. This in order to reduce the travel times of the operators to the lower levels of the mine; and that the operation of the emergency braking system complies with the safety standards required for personnel lifting equipment on inclined planes. Which will bring safety benefits to more than 1000 workers and an increase in credibility and improved reliability in the company.